Pengaruh Hybrid Ai-Human Cybercounseling Terhadap Academic Burnout Dan Psychological Well-Being: The Effect of Hybrid Ai-Human Cybercounseling on Academic Burnout and Psychological Well-Being - Yovian Yustiko Prasetya; Akhmad Musyid Hafizudin; Fernandio Irzam Nugroho; Nur Shofi Rizqika A; Kamil Fauzan; Rosa Amalia Rahmaningsih (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2022)
Global students face a mental health crisis driven by academic pressure and uncertainty about the future, increasing their vulnerability to burnout and decreasing their psychological well-being. The service gap in Indonesia, with a counselor-to-student ratio of 1:700, urges the need for innovative solutions such as artificial intelligence (AI)-based cybercounseling. A hybrid AI-human counselor model promises effectiveness and scalability, but its impact on academic burnout and psychological well-being in the Indonesian context has not been thoroughly tested. This quasi-experimental pretest-posttest study involved 50 students from the Guidance and Counseling Department at Pancasakti University in Tegal. The experimental group received hybrid AI-human cybercounseling intervention (4 sessions/2 weeks), while the control group received conventional cybercounseling. Instruments: Maslach Burnout Inventory–Student Survey (MBI-SS) and Ryff Psychological Well-Being Scale. Data were analyzed using paired-sample t-test and ANCOVA, enriched with qualitative interviews. The experimental group showed a significant decrease (*p* < 0.01) in burnout scores (MBI-SS) of 27% (Pretest: 68.20 ± 6.1; Posttest: 49.85 ± 5.3) and an increase in psychological well-being scores of 20. 7% (Pretest: 54.10 ± 7.5; Posttest: 65.30 ± 6.2). The control group did not show significant changes. Qualitative analysis revealed the mechanisms of success: (1) flexibility of time and 24/7 access through AI, (2) emotional validation and reflective deepening by human counselors, and (3) increased psychological safety. As many as 88% of participants expressed a desire to continue using the hybrid service. Hybrid AI-human cybercounseling has proven effective in significantly reducing academic burnout and improving students' psychological well-being, with high acceptance rates. This model addresses service gaps in Indonesia by combining the efficiency of AI with the depth of human intervention, offering a scalable, affordable, and sustainable solution to the student mental health crisis.